Pemanfaatan Teks Bermuatan Kearifan Lokal Dalam Meningkatkan Kemampuan Membaca Pemahaman Siswa Sekolah Dasar - Mega Prasrihamni; David Budi Irawan; Nora Surmilasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the utilization of local wisdom-based texts in the reading comprehension process in grade V at SDN 20 Banyuasin III. The research employs a descriptive qualitative method with one teacher and 28 students as subjects. Data were collected through observation, interviews, and documentation, and then analyzed through reduction, presentation, and conclusion drawing. The findings indicate that texts focused on local wisdom, reflecting the traditions and social activities of the community, can enhance student participation, motivation, and comprehension. The pre-reading stage activates prior knowledge, the while-reading stage facilitates understanding of the main ideas, and the post-reading stage encourages reflection on social and cultural values. In conclusion, the integration of local wisdom is effective in strengthening reading skills, text comprehension, and the formation of student character. Keywords: reading comprehension, local wisdom, contextual learning, literacy